Numerical simulations of the current state of waters and sea ice in the Arctic Ocean - E. N. Golubeva; G. A. Platov; D. F. Iakshina (Лëд и снег, 2015)
The paper presents results of numerical simulation of variability of the sea ice area and water circulation in the Arctic Ocean performed with use of the atmosphere reanalysis data for the period from middle of the last century to the present time. The model results reflect the ocean responses to changes of the atmosphere circulation regimes that manifests in changes of trajectories of waters coming into the Arctic Ocean from the Pacific and Atlantic oceans. The model results show influence of the Pacific and Atlantic waters on distribution and thickness of the Arctic ice.